A descrição da diversidade global de morcegos e a lacuna linneana - Gonzaga, Alice Francener Nogueira (2013)
Estimates of life on earth vary by tens of thousands and it has been claimed that there are yet a lot of species to be discovered .Taxonomy seeks to reduce this shortfall, by discovering and describing new species, but its an imperfect process that contains many types of errors. The historical pace of how the Linnean shortfall is being overcome has been temporally uneven rather than gradual. It depends on a number of factors, mainly the ones related to “who does it” (taxonomists), “how is it done” (methodologies), and “where is it done” (regions). Here we aim to point out these factors and their influences on how we have been overcoming (in time) the Linnean shortfall for bats (Chiroptera), the pace by which we do it and that of the errors that come together with it. To verify the effort in the rates of description we calculated the number of active taxonomists and the number of species described by taxonomists. To explore the completeness of bat taxonomy, we generated cumulative curves of species described per year, for both valid species and synonyms. To predict the number of species, and to see how our predictions are accurate in time and the differences between them, we adjusted the Clench function to the cumulative curve of species by regions in different periods of time. A total of 1220 species of bats are currently accepted, and of total species described 27.2% have been synonymized by now. The number of active taxonomists has been increasing exponentially through time but the number of species described per taxonomist has decreased. In the last decade, 37% of species have been described using molecular tools. The 5 total cumulative curve and most of biogeographic regions had not reached an asymptote yet and, in general, we could not make meaningful estimates of species richness. Overcoming the Linnean shortfall for bats has neither been steady in time nor has reaches an asymptote yet, evidencing that there are more species to be known. We should continue doing predictions but knowing that the factors and errors pointed here could influence the estimates.